The Times of Archaeology and Archaeologies of Time - Andrew Gardner (Papers from the Institute of Archaeology, 2001)
The subject matter of archaeology as a discipline is explicitly structured by time, and ‘timetravel’ is a common feature of popular discourses about the study of the past. Yet archaeology is also the discipline which, amongst its other theoretical shortcomings, has singularly failed to develop any theory of time. Chronology is ever-present as a measuring tool, but only in rare cases has there been any consideration of this as but one, culturally-specific kind of temporality among many others experienced by people in their daily lives. In this paper, I will discuss various perspectives on archaeological times, including more sophisticated approaches developed since the later 1980s, and argue for an abandoning of the dualism between ‘measured’ and ‘experienced’ times which has emerged in some of these more critical attempts to grapple with the issue. Time is fundamental to archaeology, but not just because we ‘use’ dates. Rather, archaeologists should be able to contribute to wider discussions of time from their understandings of the materialized temporalities of past human agents, and to develop perspectives on the importance of these to the very nature of human social agency as a form of engagement with the world.
Keywords: Theory